Surface texture change on-demand and microfluidic devices based on thickness mode actuation of dielectric elastomer actuators (DEAs) - Ankit, Ankit (2019)
Tactile feedback devices and microfluidic devices have huge significance in strengthening the area of robotics, human machine interaction and low cost healthcare. Dielectric Elastomer Actuators (DEAs) are an attractive alternative for both the areas; offering the advantage of low cost and simplistic fabrication in addition to the high actuation strains. The inplane deformations produced by the DEAs can be used to produce out-of-plane deformations by what is known as the thickness mode actuation of DEAs. The thickness mode actuation is achieved by adhering a soft passive layer to the DEA. This enables a wide area of applications in tactile applications without the need of complex systems and multiple actuators. But the thickness mode actuation has not been explored enough to understand how the deformations can be improved without altering the material properties; which is often accompanied with increased cost and a trade off with other closely associated material properties. We have shown the effect of dimensions of active region and non-active region in manipulating the out-of-plane deformation. Making use of this, we have been able to demonstrate large area devices and complex patterns on the passive top layer for the surface texture change on-demand applications. We have also been able to demonstrate on-demand microfluidic channels and micro-chambers without the need of actually fabricating the channels; which is a cost incurring and cumbersome process.